Formation of Zaminsuv River and Distribution Through the Years. - Musayev A.U (Zien Journals, 2023)
This article presents the results and analysis of the formation and classification of floodplain rivers over the years. Key terms, methodology, research objectives, and approaches are identified to analyze the formation of floodplain rivers. The article is based on research conducted to understand the classification of floodplain rivers over the years. The obtained results and their interpretation are presented. Furthermore, the main findings related to the formation of floodplain rivers and their classification over the years are discussed. The analysis includes the examination of factors indicating the affiliation of rivers to a particular type based on the conditions of river convergence.
Keywords: floodplain; river; water issues; sedimentation